Self-organization of cyclic selenaethers to yield columnar structures - Werz, Daniel B.; Rausch, Bernhard J.; Gleiter, Rolf (Tetrahedron letters, 2002)
The previously published X-ray structures of five cyclic selenaethers (1–5) revealed columnar arrangements in the solid state. In most cases (1–4) the distances between the chalcogen centers of neighboring stacks are shorter than the sum of the van der Waals radii. This is the first time that rather flexible saturated cyclic compounds were reported to form three-dimensional columnar structures due to non-bonding chalcogen–chalcogen interactions in the solid state.
Gesehen am 13.11.2020